Seismic site classification of the Costa Rican Strong-Motion Network based on Vs30 measurements and site fundamental period - Pinzón Ureña, Luis (2022)
In this paper, the soil profile of the Costa Rican Strong-Motion Network (CRSMN) stations is classified based on actual measurements and seismic regulations. The soil classification of the Costa Rican Seismic Code based on the average shear-wave velocity of the top 30 m (VS30) is used as a reference. The site fundamental period (Tf ) is included as a parameter to complement the existing characterization. For this, VS30 measurements from 52 accelerometric stations are related to the site fundamental period obtained through horizontal-to-vertical spectral ratios (HVSR) using ground motion records from the Costa Rican Strong-Motion Database. The H/V ratios are estimated with 5% damped acceleration response spectra and with traditional Fourier amplitude spectra from the S-wave window. From the relation between VS30 and Tf, different ranges of Tf are assigned to the existing soil profile classification and a graph with three-lines and four-areas is proposed to classify the stations of the CRSMN. These lines are plotted from the intersection between values assigned to each site class. The assigned classification at each station will be the one corresponding to the area where the pair of values (VS30 – Tf) falls. With this proposal, both parameters take relevance and are compensated, reducing the differences due to possible errors in measurements or interpretations.